Respuesta :

Answer:

(v + 5)(2v + 1)

Step-by-step explanation:

Given

2v² + 11v + 5

Consider the factors of the product of the coefficient of the v² term and the constant term which sum to give the coefficient of the v- term.

product = 2 × 5 = 10 and sum = + 11

The factors are + 10 and + 1

Use these factors to split the v- term

2v² + 10v + v + 5 ( factor the first/second and third/fourth terms )

= 2v(v + 5) + 1(v + 5) ← factor out (v + 5) from each term

= (v + 5)(2v + 1) ← in factored form

(V+5)(2v+1) is the answer